2012
DOI: 10.1007/s10535-012-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water deficit and excess copper on proline metabolism in Nicotiana benthamiana

Abstract: Fluctuation in proline content is a widespread phenomenon among plants in response to heavy metal stress. To distinguish between the participation of water deficit and copper on changes in proline metabolism, potted plants and floating leaf discs of tobacco were subjected to CuSO4 treatments. The application of copper increased the proline content in the leaves concomitantly with decreased leaf relative water content and increased abscisic acid (ABA) content in the potted plant. Excess copper increased the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…The lower reductions of ABA concentrations 3 and 5 days after fertilization were observed after ammonium nitrogen application, mainly after injection application. Abscisic acid is thought to play an important role in proline accumulation (Ku et al 2012). Our results are in agreement with this observation.…”
Section: Resultssupporting
confidence: 93%
“…The lower reductions of ABA concentrations 3 and 5 days after fertilization were observed after ammonium nitrogen application, mainly after injection application. Abscisic acid is thought to play an important role in proline accumulation (Ku et al 2012). Our results are in agreement with this observation.…”
Section: Resultssupporting
confidence: 93%
“…Free proline accumulation in the leaves under stress conditions is of utmost importance for plant adaptation during stress [48,49]. Our data suggests that proline content increased in zoysiagrass for all pretreatments under drought (Figure 7B).…”
Section: Discussionmentioning
confidence: 60%
“…The increased proline content in maize cultivars exposed to copper stress may be associated with the response to water deficit. Indeed, excess Cu-induced accumulation of proline has been recorded in various plants such as Oryza sativa (Chen et al, 2001 ) and Nicotiana benthamiana (Ku et al, 2012 ). We also observed that proline accumulation was high in the plants treated with H 2 O 2 in two maize cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, proline content increased in plants when exposed to wide variety of environmental stresses and thus provided the plants protection against damage by reactive oxygen species (Aspinall and Paleg, 1981 ). For instance, excess copper induced accumulation of proline in various plants such as Oryza sativa (Chen et al, 2001 ) and Nicotiana benthamiana (Ku et al, 2012 ). Adversely, it has been shown a decrease in soluble protein level at several stress condition like copper and aluminum stresses (Yadav et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%